Densidade e preferências de habitat de mamíferos em um fragmento de Mata Atlântica no Nordeste do Brasil - Albuquerque, Natasha Moraes de (2016)
Mammals play a fundamental part in the maintenance of the environment in which they live in, their many ecological interactions act as important regulators of diversity in Tropical Forests. An “ecologically fit” mammal community preserves a higher number of essential ecological relationships that sustain the biodiversity. In this sense, mammal population studies, such as density and its relations to habitat structure, might indicate the conservation status of a community in an area, allowing the formulation of improved conservation strategies. Mammal densities are influenced by a series of factors: (1) intrinsic, such as biomass and niche requirements; (2) ecological relations, as competitive exclusion; and, (3) of habitat, such as structure and quality. The present study aimed to estimate the large and medium-sized mammal densities in an Atlantic Forest remnant, and verify possible habitat preferences. The study area, Fazenda Rio Fundo (FRF), is an 800ha arboreal Restinga fragment, with a great variety of habitats. Between june 2015 and march 2016, 401 km were walked in four transects for the census method. For the habitat structure measure, eleven sample squares (20 x 5 m) were stablished, and DBH, canopy height and canopy openness values were registered. The floristic composition varied among the phytophysiognomies, and significant diferences of canopy height (p=0,000002) and canopy openness (p=0,03) were found between the habitats – Grota, Rebrota and Tabuleiro. We registered 96 visualisations of eight species during censos work. The species with more number of sightings were Dasyprocta sp. (n = 29; 13,07 ind./km²), Callicebus coimbrai (n = 27; 12,76 ind./km²), Callithrix jacchus (n = 21; 29,95 ind./km²) and Sapajus xanthosternos (n = 11; 4,39 ind./km²). The other four species sighted during census, had a low number of total visualisations (n ≤ 4) so were excluded from the density analysis. We indentified a preference for the Mature Forest habitat (Grota), for all analysed mammal except Dasyprocta sp. Density diferences seems to be related to habitat structure and floristic caracteristics, resource availability and the niche requirements of each species.